1994
DOI: 10.1159/000282670
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Digital Examination, Cystoscopy, Transrectal Ultrasonography and Needle Biopsy on the Concentration of Prostate-Specific Antigen

Abstract: The influence of various prostatic manipulations, including digital rectal examination, cystoscopy, transrectal ultrasonography and transrectal needle biopsy, on the serum prostatic-specific antigen (PSA) levels in 170 men, were examined. We found that digital rectal examination, cystoscopy and transrectal ultrasonography had no significant effect on PSA levels, except for transrectal needle biopsy, which caused an immediate increase of serum PSA in 96.2% of the patients lasting more than 2 weeks in 42.3% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Data from prior studies evaluating PSA change in relation to Table 3 Statistical comparison of total serum PSA levels at 0 and 24 h post CPE cystoscopy have shown variable results, as serum PSA level may either increase or remain the same following cystoscopy. We believe, while it is well accepted, that no urologist may consider an elevated PSA after CPE to be pathological; nevertheless, there is scarcity in published studies evaluating the precise effect of rigid cystoscopy on serum PSA levels, as a recent review of literature suggests that the serum PSA level may increase or remain unaltered following rigid cystoscopy (Table 4) [18,[25][26][27][28][29][30][31][32][33][34]. While the effect of rigid cystoscopy on serum PSA has not been clearly defined in the published literature (Table 4), in our study, we observed a significant rise in the serum PSA levels both at 1 and 24 h following cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Data from prior studies evaluating PSA change in relation to Table 3 Statistical comparison of total serum PSA levels at 0 and 24 h post CPE cystoscopy have shown variable results, as serum PSA level may either increase or remain the same following cystoscopy. We believe, while it is well accepted, that no urologist may consider an elevated PSA after CPE to be pathological; nevertheless, there is scarcity in published studies evaluating the precise effect of rigid cystoscopy on serum PSA levels, as a recent review of literature suggests that the serum PSA level may increase or remain unaltered following rigid cystoscopy (Table 4) [18,[25][26][27][28][29][30][31][32][33][34]. While the effect of rigid cystoscopy on serum PSA has not been clearly defined in the published literature (Table 4), in our study, we observed a significant rise in the serum PSA levels both at 1 and 24 h following cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple investigators have demonstrated that routine DRE causes a statistically significant elevation in PSA levels, but that this elevation is small and usually not clinically significant [75][76][77]. Since post-DRE serum PSA elevations tend to be greater in men with baseline PSA levels > 4.0 ng/ml (i.e., those men with an indication for prostate biopsy), clinical decision making is usually not affected [78].…”
Section: Manipulation Instrumentation and Surgerymentioning
confidence: 99%
“…More aggressive manipulation of the prostate (i.e., prostate massage) does seem to increase PSA levels as early as one hour after massage to levels as high as twice baseline [79]. Similar to routine DRE, transrectal ultrasonography (without biopsy), urethral catheterization and a traumatic cystoscopy do not produce clinically significant alterations in serum PSA levels [77,80,81].…”
Section: Manipulation Instrumentation and Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, especially in cases with PSA values between 2, and 10 ng/mL where PSA values of benign prostatic hyperplasia (BPH), and PCa overlap, application of biopsy procedure contributes adversely to subsequent treatment burden. [8,9] Therefore in the early diagnosis of PCa, biomarkers with higher sensitivity, and specificity are needed without resorting to invasive interventions.…”
Section: Introductionmentioning
confidence: 99%